Studi Pendahuluan: Peningkatan Kesejahteraan Masyarakat Pesisir Surabaya melalui Inovasi Olah Mangrove sebagai Tanaman Hias - Iska Desmawati; Muhammad Nasrulloh; Suratno (Institut Teknologi Sepuluh Nopember, 2019)
Surabaya, one of the big cities in Indonesia which has a large coastal area. Thiscoastal area has a lot of potential for high biodiversity, mainly mangroves. Thisstudy aims to know the first study about potential mangroves, media, and designfor the new concept from mangrove products. Based on this study, we know thatmangroves that have good potential are Rhizophora mucronata, Avicennia marina,and Bruguiera gymnorhiza. The media used for this study are clay, sand, and localmoss. Design for this houseplant could be modified from kokedama. The resultfrom this study will continue to the laboratorium and acclimation step and willname it “MangroveBall” as an icon of tourism from the coastal area in Surabayaand increase the local economy for the society.